Pengaruh Kemampuan Kognitif Mahasiswa MPI terhadap Pemahaman Teori-Teori Perilaku dan Budaya Organisasi (Studi Kasus Kelas C MPI) - Yayuk Purwati; Heru Sulistya; Sedya Santosa (LPPM IAINU Kebumen, 2021)
This study is about the influence of students' cognitive abilities on the understanding of behavioral theories and organizational culture in the Islamic Education Management education program class C UIN Sunan Kalijaga Yogyakarta. This study involved students in MPI C class who had attended lectures on Organizational Behavior and Culture courses. This research method using survey research with quantitative approach. Intrumen research using questionnaires that have been shared on Google Form to measure students' cognitive abilities to understand behavioral theories and organizational culture. Based on the results of the study, data obtained that cognitive ability of students influenced the understanding of organizational behavior theories and organizational culture as much as 22.3% while the remaining 77.7% influenced by other variables. There was an increase in students' cognitive abilities through the learning process of behavioral courses and organizational culture with correlations ranging from 0.48.